Things rejudicated in proceedings with a declaration of an unconstitutional state of affairs: effects of judicial decisions with an unconstitutional state of affairs and their relationship with collective proceedings (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The general aim of this study is to look at the effects of court decisions in cases declared unconstitutional in relation to collective proceedings, especially considering their importance in protecting the rights of the community involved, in order to contribute to improving the justice system and strengthening the defense of collective rights. The problem arose from the realization that lawsuits are instruments that seek to resolve conflicts; however, considering that there are countless demands and disputes within society, it was questioned whether there would be different solutions to a specific case. To carry out the research, the deductive method was used, with a qualitative approach, based on bibliographical and documentary research. In order to achieve the proposed objectives, the article covers the following topics: a) the relevance of judicial decisions in protecting fundamental rights; b) the theoretical and conceptual foundations of collective proceedings and the effects of judicial decisions; c) the effects of proceedings declared unconstitutional and their relationship with collective proceedings. In this study, it was found that, considering that collective rights are divided into diffuse rights, collective rights and individual homogeneous rights, each with various effects and particularities; the anomalous effects of decisions in collective proceedings must be verified, depending on the type of right involved, showing a broad relationship between collective proceedings and proceedings with a declaration of unconstitutional state of affairs, as legal instruments for resolving systemic violations, the effects of which can go beyond the sphere of rights of the plaintiffs.
Keywords: judicial process; collective law; unconstitutional state of affairs; res judicata; effects